Chinese Herbal Medicine in the Treatment of Depression in Parkinson’s Disease: From Molecules to Systems - Zhang, Yi; Xu, Xiaoman (Frontiers in Pharmacology, 2022)
Depression is one of the most common non-motor symptoms in patients with Parkinson’s disease (PD). Depression in PD (DPD) increases the disability rate and reduces the quality of life of PD patients and increases the caregiver burden. Although previous studies have explained the relationship between depression and PD through a variety of pathological mechanisms, whether depression is a precursor or an independent risk factor for PD remains unclear. Additionally, increasing evidence shows that conventional anti-PD drug therapy is not ideal for DPD. Traditional Chinese medicine (TCM) prescriptions exhibit the characteristics of multi-target, multi-pathway, and multi-level treatment of DPD and may simultaneously improve the motor symptoms of PD patients through multiple mechanisms. However, the specific pharmacological mechanisms of these TCM prescriptions remain unelucidated. Here, we investigated the mechanisms of action of the active ingredients of single herbs predominantly used in TCM prescriptions for depression as well as the therapeutic effect of TCM prescriptions on DPD. This review may facilitate the design of new selective and effective treatment strategies for DPD.